Changes in methylation of transcribed and satellite areas of the genome during aging the cotyledon leaves of Linum usitatissimum exposed to X-ray radiation - Berestyana A. М.; Grodzinsky, D. M. (Reports of the National Academy of Sciences of Ukraine, 2015)
The effect of X-irradiation on the DNA methylation status of cotyledon leaves Linum usitatissimum in the aging is studied. The changes in the methylation profile of functionally different parts of the genome at certain doses and in the process of aging are found. Hypothetical epigenetic mechanisms of response to ionizing radiation are considered.